2018
DOI: 10.1155/2018/5851914
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive Environment Attenuation during Adult Mouse Optic Nerve Regeneration

Abstract: The regenerative capacity of CNS tracts has ever been a great hurdle to regenerative medicine. Although recent studies have described strategies to stimulate retinal ganglion cells (RGCs) to regenerate axons through the optic nerve, it still remains to be elucidated how these therapies modulate the inhibitory environment of CNS. Thus, the present work investigated the environmental content of the repulsive axon guidance cues, such as Sema3D and its receptors, myelin debris, and astrogliosis, within the regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…(Moore et al, 2009 ; Belin et al, 2015 ; Wang et al, 2018 ). More recently, combinatorial approaches via modulating multiple independent pathways have been shown to promote injured axons to regenerate beyond the optic chiasm into the brain and reform functional synapses with their original targets (Lim et al, 2016 ; Goulart et al, 2018 ). For example, visual stimulation/RHEB1 overexpression led to regenerating axons back to almost all the correct targets.…”
Section: Introductionmentioning
confidence: 99%
“…(Moore et al, 2009 ; Belin et al, 2015 ; Wang et al, 2018 ). More recently, combinatorial approaches via modulating multiple independent pathways have been shown to promote injured axons to regenerate beyond the optic chiasm into the brain and reform functional synapses with their original targets (Lim et al, 2016 ; Goulart et al, 2018 ). For example, visual stimulation/RHEB1 overexpression led to regenerating axons back to almost all the correct targets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study showed that Sema3D and PlexinA1 levels were significantly reduced when zymosan and cAMP analog were used to promote regeneration of crushed optic nerve in a rodent model [ 45 ]. Their result is in concert with our finding of loss of dendritic spine by Sema3D over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…Leaving aside experiments analyzing the different guidance cues expression levels, there are a few gain- and loss- of function experiments analyzing the function of the different guidance cues in axon regeneration. Sema3D, and the receptor PlexinA1, are downregulated in KO:PTEN mice, which are able to regenerate the optical nerve after crush [ 203 ], while another study shows how transgenic mice with mutant PlexinA3 and PlexinA4 showed no regenerative improvements after mice SCI [ 204 ]. In goldfish, Netrin-1 was found binding to RGC regenerative axons, suggesting that these neurons expressing Netrin receptors had a possible role in this signaling during regeneration [ 205 ].…”
Section: Guidance Cues In Axotomy and Axon Regenerationmentioning
confidence: 99%